1988
DOI: 10.1037/0097-7403.14.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of a CS–US association by a US–US association.

Abstract: Pigeons were autoshapcd with a keylight as the conditioned stimulus (CS) and food as the unconditioned stimulus (US). Preexposure to repeated US presentations was followed by training sessions in which a single US preceded a single CS-US pairing. Preexposure blocked conditioning to the CS only when the interval between the prior US and the US in the CS-US pairing (critical interval) was equal to the US-US interval in preexposure. Blocking was examined as a function of the length of the critical interval and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 39 publications
5
40
0
Order By: Relevance
“…It is possible that the response rate in the stimulus was determined by conditioning to the CS-US interval (Bitterman, 1964;Black, 1963;Gibbon et aI., 1977;Salafia et aI., 1975;Schneiderman & Gormezano, 1964), and the response rate in the nonstimulus period was determined by conditioning to the context (Goddard & Jenkins, 1988;Tomie, 1981). These two associative mechanisms could in principle produce higher response rates during the stimulus to shorter stimulus durations (right panels of Figure 4) and higher response rates during the non stimulus to shorter cycle durations (left panels of Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the response rate in the stimulus was determined by conditioning to the CS-US interval (Bitterman, 1964;Black, 1963;Gibbon et aI., 1977;Salafia et aI., 1975;Schneiderman & Gormezano, 1964), and the response rate in the nonstimulus period was determined by conditioning to the context (Goddard & Jenkins, 1988;Tomie, 1981). These two associative mechanisms could in principle produce higher response rates during the stimulus to shorter stimulus durations (right panels of Figure 4) and higher response rates during the non stimulus to shorter cycle durations (left panels of Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The added variability does not change the density of food delivery, which presumably affects the strength of context conditioning (Goddard & Jenkins, 1988;Tomie, 1981); it also does not alter the degree to which the temporal cue predicts food delivery in advance of the onset of the stimulus. If either of these factors is important in determining the salience of the temporal cue, then we would expect to replicate the results of Experiment 1, even with the addition of variability to the food-food interval.…”
Section: Methodsmentioning
confidence: 99%
“…The conditioning literature has found that typical unconditioned stimuli can serve as predictors of other stimuli. For example, Goddard and Jenkins (1988) showed that if food appears at a regular schedule, one feeding event is learned to predict a subsequent event. Furthermore, this learning blocked the learning of another cue’s prediction of feeding.…”
mentioning
confidence: 99%